Consumers' response to product changes to improve healthiness - Kurash, Olha; San José Iglesias, Rafael; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor’s thesis examines consumer responses to health-oriented modifications of food products, focusing on four types of reformulations: gluten-free, sugar-free, lactose-free, and high-protein. Using a combination of literature review and original quantitative research based on four online surveys, the study explores how such formulations influence perceptions of attractiveness, innovativeness, nutritional value, and purchasing intention. It also investigates which factors guide consumers when selecting food products and how demographic characteristics shape attitudes and behaviors. The findings suggest that nutritional value and quality of ingredients play a central role in purchase decisions. Age, educational level, and household income significantly influence behavior. The study offers recommendations for producers and marketers aiming to develop or improve health-modified food products in an increasingly nutrition-conscious market.
Vedoucí práce: Rafael San José Iglesias
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses